Association Between Disability and Suicide Mortality in the Spanish Community-Dwelling Adult Population. A Population-Based Follow-Up Study - Roberto Pastor-Barriuso; Roberto Pastor-Barriuso; Alicia Padrón-Monedero; Javier Almazán-Isla; Javier Almazán-Isla; Fernando J. García López; Fernando J. García López; Jesús de Pedro-Cuesta; Jesús de Pedro-Cuesta; Javier Damián; Javier Damián (Frontiers Media S.A., 2024)
ObjectivesTo assess the association of disability with suicide mortality, separately for women and men by age group.MethodsInformation was obtained from a representative national sample of 161,809 community-dwelling adults (≥18 years). Participants contributed to follow-up time from baseline interview (2008) until suicide, death by other causes, or 2017. We calculated, by sex, standardized suicide mortality differences (SSMD), comparing persons with and without disabilities standardized to sociodemographic distribution of disability population.Results29 women died by suicide during 800,754 person-years follow-up and 97 men during 735,709 person-years. Among women with disabilities, SSMD (95% Confidence interval) per 100,000 person-years at 5 years was 54.4 deaths (−17.2 to 126.1) [100.0 (−27.4 to 227.4) in women <65 years and −4.8 (−27.3 to 17.7) in women ≥65 years (P homogeneity = 0.11)]. Among men, SSMD increased by 122.2 deaths (4.1 to 240.3) [37.2 (−40.2 to 114.6) in men <65 years and 74.7 (−51.8 to 200.5) in men ≥65 years (P homogeneity = 0.62)].ConclusionSuicide risk was higher in women and men with disability. In women higher risk was only notable for those <65. Men presented similar effects in both age groups. Nevertheless, due to imprecision of estimates, results should be viewed cautiously.